PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN DIVISI CSSD RUMAH SAKIT UMUM DAERAH PASAR MINGGU - Yudi Tirto Aji; Jublina Oktora (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work discipline and work environment on the performance of employees at the Pasar Minggu area general hospital. The type of research used is a quantitative approach. The population and sample in this study were all employees of the Pasar Minggu area general hospital, totaling 50 people. The data collection method in this research uses a questionnaire. And the results of this research are that work discipline (X1) has a positive and significant value on employee performance (Y) at Pasar Minggu Hospital. This can be proven through the t test which has a t value of 2.136 and a t table value of 2.0117, with a sig level of 0.0038 < 0.05, which means that work discipline has a positive influence on employee performance. The work environment (X2) has a positive and significant value on employee performance (Y) at Pasar Minggu Hospital. This can be proven through the t test which has a calculated value of 3.009 and a value of 2.0117, with a sig level of 0.00 < 0.05, meaning that the work environment has a positive influence on employee performance. The variables of work discipline and work environment simultaneously show the results have a significant effect on the performance variable. employees at Pasar Minggu Hospital employees. This is proven by the results of the simultaneous hypothesis test, the F test obtained f count > f table 5,137 > 3,191 and a significance value of 0.001 < 0.05.